Dancing with Disaster : Environmental Histories, Narratives, and Ethics for Perilous Times - Rigby, Catherine E. (Book collections on Project MUSE., 2015)
"The calamitous impacts of climate change that are beginning to be felt around the world today expose the inextricability of human and natural histories. Arguing for a more complex account of such calamities, Kate Rigby examines a variety of past disasters, from the Black Death of the Middle Ages to the mega-hurricanes of the twenty-first century, revealing the dynamic interaction of diverse human and nonhuman factors in their causation, unfolding, and aftermath. Focusing on the link between the ways disasters are framed by the stories told about them and how people tend to respond to them in practice, Rigby also shows how works of narrative fiction invite ethical reflection on human relations with one another, with our often unruly earthly environs, and with other species in the face of eco-catastrophe. In its investigation of an array of authors from the Romantic period to the present--including Heinrich von Kleist, Mary Shelley, Theodor Storm, Colin Thiele, and Alexis Wright--Dancing with Disaster demonstrates the importance of the environmental humanities in the development of more creative, compassionate, ecologically oriented, and socially just responses to the perils and possibilities of the Anthropocene."--Publisher's description